War crimes tribunals and transitional justice the Tokyo trial and the Nuremburg legacy - Futamura, Madoka (Contemporary security studies, 2008)
Examines the short- and long-term impact of the International Military Tribunal for the Far East (the Tokyo Trial), on post-war Japan, in order to improve the understanding of and strategy for international war crimes tribunals. This book is of interest to students of war crimes, international law, transitional justice and international relations